2015
DOI: 10.1002/da.22401
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Cortical Thickness and Serum Cortisol Levels in Drug-Naïve, First-Episode Patients With Major Depressive Disorder: A Surface-Based Morphometric Study

Abstract: In the early stage of MDD, the thickness of the lateral orbitofrontal cortex was significantly reduced, and also showed a significant inverse correlation with the serum cortisol levels. Since the lateral orbitofrontal cortex contains a high concentration of glucocorticoid receptor, glucocorticoid receptor-mediated signaling transductions could contribute to neurotoxicity, which might occur when there are high cortisol levels in patients with MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 43 publications
6
33
3
Order By: Relevance
“…The lower medial wall of the PFC (medial OFC according to the Desikan–Killiany atlas 21 in FreeSurfer) contains the subgenual ACC (sgACC), subcallosal gyrus and medial OFC and has dense connections to the hypothalamus as the primary site of stress response regulation. 31 These findings concur with postmortem findings of OFC structural deficits, 32 OFC/sgACC-specific volumetric meta-analyses, 8, 33 correlations between OFC thickness and cortisol levels 34 and evidence of functional derangement of the sgACC in depression. 35 Recently, right medial OFC thickness measured at baseline in healthy adolescent girls proved a strong predictor of the onset of depression in a multivariate model.…”
Section: Discussionsupporting
confidence: 54%
“…The lower medial wall of the PFC (medial OFC according to the Desikan–Killiany atlas 21 in FreeSurfer) contains the subgenual ACC (sgACC), subcallosal gyrus and medial OFC and has dense connections to the hypothalamus as the primary site of stress response regulation. 31 These findings concur with postmortem findings of OFC structural deficits, 32 OFC/sgACC-specific volumetric meta-analyses, 8, 33 correlations between OFC thickness and cortisol levels 34 and evidence of functional derangement of the sgACC in depression. 35 Recently, right medial OFC thickness measured at baseline in healthy adolescent girls proved a strong predictor of the onset of depression in a multivariate model.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, high cortisol levels may be linked to brain morphology abnormalities in MDD. Additionally, we previously reported that high cortisol levels were linked with medial orbitofrontal cortex thinning (Liu et al, 2015) and white matter tract disconnectivity in frontal-limbic and frontal-subcortical circuits, which are considered to constitute an element in the pathogenesis of MDD (Liu et al, 2016). Additionally, we previously reported that high cortisol levels were linked with medial orbitofrontal cortex thinning (Liu et al, 2015) and white matter tract disconnectivity in frontal-limbic and frontal-subcortical circuits, which are considered to constitute an element in the pathogenesis of MDD (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…The parietal lobe is involved in the organization, decision making, and predictions of rewards during conditioning that evaluates outcomes for future response choices that are uncertain . This region is also related to emotional processing and cognitive changes and is part of the default‐mode network.…”
Section: Significant Structural Brain Alterations In Mddmentioning
confidence: 99%
“…27 The right anterior cingulate cortex was reported to have a decreased magnetization transfer ratio in patients with treatment-refractory MDD relative to healthy controls, 28 which increased after electroconvulsive therapy. 29 Previous studies have also found that prefrontal areas undergo a significant reduction in thickness, 4,[30][31][32] and these changes are thought to be associated with poor clinical outcomes. 33 A negative correlation was observed between the Montgomery-Asberg Depression Rating Scale score and cortical thickness in the ACC.…”
Section: Frontal Lobementioning
confidence: 99%